Homotopy Method for a General Multiobjective Programming Problem under Generalized Quasinormal Cone Condition - X. Zhao; S. G. Zhang; Y. T. Yang; Q. H. Liu (Abstract and Applied Analysis)
A combined interior point homotopy continuation method is proposed for solving general multiobjective programming problem. We prove the existence and convergence of a smooth homotopy path from almost any interior initial interior point to a solution of the KKT system under some basic assumptions.